Emergency dispatchers as instructors of laypersons in unplanned out-of-hospital deliveries - Interdisciplinary qualitative study - Jussi Hänninen; Hanna Toiviainen; Hilla Nordquist (PLoS ONE, 2025)
Introduction Unplanned out-of-hospital delivery tasks are continuously increasing and are challenging to the emergency dispatcher, but there is scant research on them, especially from the perspective of instructing the layperson in delivery. In the Finnish model of one emergency response centre authority, the expertise of the emergency dispatcher is highlighted. However, it’s necessary to develop collaborative and transformative expertise and cooperation in the maternity care service system to respond to risky and unexpected childbirth events. This study adopts concepts from cultural-historical activity theory in the framework of object-oriented activity systems and negotiated knotworking. Our aim is to describe and analyse the perspectives of emergency dispatchers and laypersons when the emergency dispatcher instructs the layperson in handling an unplanned out-of-hospital delivery. Methods This is an interdisciplinary qualitative study. The study data consists of stories written by emergency dispatchers (n = 31) and semi-structured interviews with laypersons (n = 5). The data was collected using both the method of empathy-based stories and semi-structured interviews. The data was analysed using qualitative theory-driven content analysis, data-based theory-driven thematic analysis and text mining. Results The emergency dispatchers’ and laypersons’ descriptions of their actions in the examined delivery situations were structured as elements of activity systems. The thematic analysis produced two themes containing discursive characteristics of negotiated knotworking, which were (i) script innovations requiring midwifery competence and (ii) emotion work. Discussion The object of the emergency dispatcher’s actions was the physical wellbeing of the person giving birth and the newborn, while the layperson’s object was the childbirth experience, including the aforementioned and shared with the person giving birth. The formal script of childbirth services does not serve negotiated knotworking. Further, a midwife’s participation in an emergency call, including video consultation, is desired. The emergency dispatcher should respect the object-oriented conscious agency of the layperson, providing ad hoc information for childbirth.